Intégrer économie et écologie : le cas de l’industrie canadienne - Jean Kabongo (VertigO)
The integration of ecology and economy in the activities of the industrial companies has been the object of several theoretical and practical considerations.  The strategies of the environmental operations often involve considerable investments for the industrial companies.  The leaders of these companies face growing constraints from the governments and the community- which require the adoption of systems of clean production- as well as consequences of the fluctuations of the markets and competition.  The studies relating to these considerations have been directed more towards the description of the conditions and the economic implications of the harmonization of the ecology and the economy of the enterprise.  Few empirical researches that attempt to describe the advance traversed by the industrial companies in this process of integration. For a better understanding this question, a study in the view of the persons in charge for twelve industrial companies that experience the practices of industrial ecology was carried out.  The results show that as well for the companies for which residual rehabilitation constitutes the core business as for those whose this rehabilitation is made in margin operations of industrial production, the integration of ecology and economy responds to a logic of increasing and diachronic profitability.  A model of the evolution of this integration is proposed.  This one is characterized by four essential stages:  conscientiousness, structuring, assertion and consolidation.